Identification of coding sequences from a freshly prepared Trypanosoma brucei brucei expression library by polymerase chain reaction - Okalang, Uthman; Nanteza, Ann; Matovu, Enock; Lubega, George W. (International Journal of Biochemistry and Molecular Biology, 2013)
Animal African trypanosomiasis (AAT) also known as Nagana is a devastating disease among domestic animals in large parts of Sub-Saharan Africa causing loses in milk and meat production as well as traction power. However, there is currently no commercial vaccine against AAT. The parasites have also developed resistance to some of the drugs in use. Moreover, the use of affordable computer-aided wet bench methods in the search for vaccine and/or new drug targets against this disease have not yet been fully explored in developing countries. This study, therefore, explored the use of PCR to screen a freshly prepared bloodstream form Trypanosoma brucei brucei (T. b. brucei) expression library for coding sequences followed by bioinformatics analyses specifying the functions and importance of these proteins to parasite survival. Eleven protein coding sequences were identified from twenty nine purified clones. The putative retro transposon hot spot protein 4 (RHSP 4) was the only protein with a fully annotated DNA sequence. All the others were hypothetical or had partial or unqualified annotations. RHSP 4 and pyruvate dehydrogenase E1 component, alpha sub-unit (PDE1α) are involved in aerobic respiration whereas succinyl-Co A-3-ketoacid-coenzyme A transferase mitochondrial precursor (SKTMP) is predicted to be involved in ketone body catabolism. Cystathionine beta-synthase (CBS) and alpha-1,3-mannosyltransferase (αMT) have been predicted in cysteine biosynthesis and vesicular transport respectively. The functions of the hypothetical proteins encountered have neither been experimentally determined nor predicted. We hypothesize that both CBS and PDE1α are good drug targets. Overall, about 300 plates are required to PCR screen the entire Trypanosoma brucei genome in approximately eight months. This method is therefore, applicable and affordable in the search for new drug targets under conditions of limited resources among developing countries.
Keywords: drug targets; proteins; expression library; PCR; bioinformatics; Nagana